Automation of Animal Feeders Using NODEMCU ESP8266 and Smartphone-Based BLYNK APP - Dali Purwanto, Timur; Effendy, Irman; Naldo, Vio (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Most humans today have used smartphones or smartphones, and besides that, humans also have pets where these pets require routine care, such as feeding the pet and others. We as humans sometimes when are not available or unable to care for our pets. Therefore the author raises the title